A magyar mondatszerkezet leírása HPSG keretben - Szécsényi P. Tibor (Acta Universitatis Szegediensis : sectio ethnographica et linguistica = néprajz és nyelvtudomány = étnografiâ i azykoznanie = Volkskunde und Sprachwissenschaft, 1997)
So far a transformational model has been used for the description of the topicfocus-verb order in Hungarian sentence structure. The present paper offers a new, non-transformational approach within the framework of Head-Driven Phrase Structure Grammar (HPSG). According to my suggestion sentence structure in Hungarian is non-configurational, the positions of topics and foci are determined by a small number of lexical features and linear precedence rules. The resulting structures, including infinitival constructions, are flat. The method described in the paper is at the same time a useful device for the treatment of discontinuous constituents.